NMR-driven identification of anti-amyloidogenic compounds in green and roasted coffee extracts. (30th June 2018) - Ciaramelli, Carlotta; Palmioli, Alessandro; De Luigi, Ada; Colombo, Laura; Sala, Gessica; Riva, Chiara; Zoia, Chiara Paola; Salmona, Mario; Airoldi, Cristina
Highlights: NMR allows to identify amyloid ligands and inhibitors in complex food matrixes. Green and roasted coffee extracts show a "multi-target" anti-amyloidogenic activity. Coffee extracts hinder Aβ peptide aggregation and cytotoxicity in a human cell line. Coffee extracts reduce oxidative stress and modulate autophagy in a human cell line. Chlorogenic acids and melanoidins are the most active components of coffee extracts. Abstract: To identify food and beverages that provide the regular intake of natural compounds capable of interfering with toxic amyloidogenic aggregates, we developed an experimental protocol that combines NMR spectroscopy and atomic force microscopy, in vitro biochemical and cell assays to detect anti-Aβ molecules in natural edible matrices. We applied this approach to investigate the potential anti-amyloidogenic properties of coffee and its molecular constituents. Our data showed that green and roasted coffee extracts and their main components, 5- O -caffeoylquinic acid and melanoidins, can hinder Aβ on-pathway aggregation and toxicity in a human neuroblastoma SH-SY5Y cell line. Coffee extracts and melanoidins also counteract hydrogen peroxide- and rotenone-induced cytotoxicity and modulate some autophagic pathways in the same cell line.